Tourists' perceptions of climate change impact in Rovaniemi, Finland - Makeionok, Valeriia (fi=Lapin yliopisto|en=University of Lapland|, 2024)
Rovaniemi, a popular destination for Arctic tourism is facing significant challenges due to the climate change. The shift in weather patterns is impacting the winter tourism industry, altering the traditional appeal of a destination and its activities. This Master thesis examines how tourists perceive the impacts of global warming and how it is influencing travel decisions, preferences, and the attractiveness of the destination. A survey distributed to the tourists in Rovaniemi during the winter months collected the data on tourirts demographics, travel background, awareness of climate change, and perceptions of the destination's attractiveness under various climate scenarios. Quantitative and qualitative analysis showed that while the image of snow plays a crucial role in tourists decision making, tourists demonstrated the flexibility in adapting their preferences in response to climate change. Promoting alternative, non-snow-related activities like the Northern Lights, wellness experiences and Santa Claus themes activities are recommended for maintaining attractiveness of Rovaniemi in times of climate change. The study provide valuable insights for future research and local decision makers in developing sustainable tourism strategies to address the challenges of climate change.